Anelastic-like nature of the rejuvenation of metallic glasses by cryogenic thermal cycling. (1st January 2023) - Costa, Miguel B.; Londoño, Juan J.; Blatter, Andreas; Hariharan, Avinash; Gebert, Annett; Carpenter, Michael A.; Greer, A. Lindsay
Abstract: Cryogenic thermal cycling (CTC) is an effective treatment for improving the room-temperature plasticity and toughness in metallic glasses. Despite considerable attention to characterizing the effects of CTC, they remain poorly understood. A prominent example is that, contrary to expectation, the stored energy in a metallic glass first rises, and then decreases, as CTC progresses. In this work, CTC is applied to bulk metallic glasses based on Pd, Pt, Ti, or Zr. The effects on calorimetric and mechanical properties are evaluated. Critically, CTC-induced effects, at whatever stage, are found to decay over about one week at room temperature after CTC, returning the properties to those of the as-cast glass. A model is proposed for CTC-induced effects, treating them as analogous to the accumulation of anelastic strain. The implications for analysis of existing data, and for future research on CTC effects, are highlighted. Graphical abstract: Image, graphical abstract